The witch - Grafius, Brandon R. (Devil's advocates., 2020)
The Witch (2015) is one of the most critically acclaimed horror films of recent years. This Devil's Advocate, the first stand-alone critical study of the film, provides the historical and religious background necessary for a fuller appreciation, as well as situating the film within a number of horror sub-genres (such as folk horror) as well as its other literary and folkloric influences.